The effect of banking regulation on cross-border lending - Fidrmuc, Jarko; Hainz, Christa (Journal of Banking & Finance, 2013)
Banking regulations often differ between countries: Some regulators require banks to document their evaluation of firms’ creditworthiness, which determines the banks’ choice of lending technology. In a theoretical model, we study how differences in regulation influence competition between domestic and foreign banks and analyze the effect of regulatory harmonization on cross-border lending. We predict that lending rates are lower and access to credit is easier for firms in a border region if the national regulations differ. Using unique bank- and firm-level data from Germany, we show that firms in a border region have better access to credit if regulation differs.